Isolated cryptococcosis of a lumbar vertebra in an immunocompetent patient: A case report and literature review - Jia, Zhongxiong; Tang, Min; Zhang, Xiaojun; Xin, Xiaojuan; Jiang, Wei; Hao, Jie (Frontiers in Surgery, 2023)
Background: Cryptococcus, a kind of fungus, can be found in soil, decayed wood, and avian excreta. Immunocompromised patients are prone to infection caused by Cryptococcus, and the lungs and central nervous system are the main target organs. Cryptococcosis rarely occurs in the lumbar vertebra or in immunocompetent patients. Case presentation: A 40-year-old adult male with isolated lumbar vertebra cryptococcosis at the L4 vertebra underwent successful lesion removal surgery performed via the posterior approach and postoperative administration of an antifungal agent. At the 12-month follow-up, the patient’s pain was relieved, and his motor function had improved. Isolated Cryptococcus vertebrae infection is a rare infectious disease. Conclusions: A needle biopsy can confirm the diagnosis of Cryptococcus infection. When patients present with unbearable symptoms of nerve compression, posterior depuration combined with postoperative antifungal agents is a good option.